Med troen som fællesnævner – fællesskab blandt unge i Indre Mission - Christensen, Tina Wilchen (Kulturstudier, 2010)
Artiklen vil belyse de mekanismer, der ligger til grund for et velfungerende fællesskab i en af Indre Missions ungdomsforeninger i Århus. Troen har på forskellige måder en central position i fællesskabet, og denne artikel vil argumentere for de unges tro som en social identitet, idet deres habitus synes at have en afgørende betydning for den og deres oplevelse af det religiøst funderede fællesskab. Artiklenvil også belyse, hvordan Biblen og dens fortællinger udgør den fortolkningsramme, som de unge er opvokset med og forstår livet igennem. Artiklen viser desuden den rolle, det kollektive samvær spiller i de unges konstruktion af Gud og egen identitet som kristen. Faith as common ground- community feeling among young evangelicals in Denmark The aim of this article is to demonstrate the mechanisms that underlie a youth association in the so-called Home Mission, a branch of the Evangelical Lutheran Church of Denmark. It is the result of anthropological research focusing on the sense of community among members aged between 15 and 27. In a number of ways faith plays a central role in the community, and the main argument of the article is that the young people's faith constitutes a social identity, since their habitus seems to have a decisive impact on their experience of the faith-based community. The article further demonstrates how the Bible and its narratives form the framework of interpretation with which the young people have grown up, and which, in their present life as adults, continues to mould their understanding and view of life, as well as the role that collective interaction plays in the young people's construction of God and their own identity as Christians. A core argument in the article is that faith is a socialization into a structure which results in all participants having the same frame of reference and therefore experiencing a strong feeling of community with one another within this particular wing of the Church of Denmark.